Highlights on distinctive structural and functional properties of HTLV Tax proteins - Romanelli, Maria G.; Diani, Erica; Bergamo, Elisa; Casoli, Claudio; Ciminale, Vincenzo; Bex, Françoise; Bertazzoni, Umberto (Frontiers in Microbiology, 2013)
Human T-cell Leukemia Viruses (HTLVs) are complex human retroviruses of the Deltaretrovirus genus. Four types have been identified thus far, with HTLV-1 and HTLV-2 much more prevalent than HTLV-3 or -4 . HTLV-1 and HTLV-2 possess strictly related genomic structures, but differ significantly in pathogenicity, as HTLV-1 is the causative agent of adult T-cell leukemia (ATL) and of HTLV associated myelopathy/tropical spastic paraparesis (HAM/TSP), whereas HTLV-2 is not associated with neoplasia. HTLVs code for a protein named Tax that is responsible for enhancing viral expression and drives cell transformation. Much effort has been invested to dissect the impact of Tax on signal transduction pathways and to identify functional differences between the HTLV Tax proteins that may explain the distinct oncogenic potential of HTLV-1 and HTLV-2. This review summarizes our current knowledge of Tax-1 and Tax-2 with emphasis on their structure, role in activation of the NF-kB pathway, and interactions with host factors.